The fossilization of non-current English pronunciation in German EFL teaching1: Why does the use of obsolete vowels persist among German speakers of English?. (2nd November 2015) - Booth, John E.
Abstract : The German term Handy is a neat and singular creation, referring to the 'mobile phone' (British English) or 'cell phone' (American English), in itself a unique and most useful invention – handy, indeed! What is even more remarkable is the pronunciation of this term: /hεndi:/. While the second vowel mirrors the pronunciation of word-final 'i' sounds in German (cf. Gabi, Salami, Müsli ), the 'a' does not. Instead, it appears to reflect a socially generalized view of what a short 'a' in English is supposed to sound like. And this is not the front, near-open 'ash' vowel [æ], the 'standard lexical set TRAP', as defined by Wells (1982: 129), but rather a cardinal [ε], the 'standard lexical set DRESS' (128), as found in German in other English borrowings: Jetlag or Jet-Lag /jεtlεg/, Gag /gεg/, relaxen /relεksn/, scannen /skεnǝn/, etc.